Narrative, intertext, and space in Euripides' Phoenissae - Lamari, Anna A. (Trends in classics. Supplementary volumes ;, 2010)
This book applies the basic principles of narratology to an ancient Greek tragedy, namely Euripides ́Phoenissae. In a play with an exceptionally rich plot, a narratological study yields interesting interpretive results regarding the use of myth, narrators, narrative levels, time and space, as well as the relation of the Phoenissae with previous treatments of the Theban mythical saga.